2019
DOI: 10.3389/fgene.2019.00511
|View full text |Cite
|
Sign up to set email alerts
|

A Trans-Ethnic Genome-Wide Association Study of Uterine Fibroids

Abstract: Uterine fibroids affect up to 77% of women by menopause and account for up to $34 billion in healthcare costs each year. Although fibroid risk is heritable, genetic risk for fibroids is not well understood. We conducted a two-stage case-control meta-analysis of genetic variants in European and African ancestry women with and without fibroids classified by a previously published algorithm requiring pelvic imaging or confirmed diagnosis. Women from seven electronic Medical Records and Genomics (eMERGE) network s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 71 publications
3
35
0
Order By: Relevance
“…Importantly, these features are not ascribed to elevated cell viability, since the lack of Luzp1 leads to a reduction in cell numbers and additionally, an increase in cell apoptosis. Our results coincide with the reported anti-proliferative effect of Luzp1 downregulation in colorectal cancer cells ( Poel et al, 2019 ) and the reported increase in proliferation due to Luzp1 upregulation in uterine fibroids ( Edwards et al, 2019 ). Considering the interaction between LUZP1 and LIMA1/EPLIN, our results mirror those showing increased metastatic potential upon loss or downregulation of the tumor suppressor EPLIN ( Jiang et al, 2008 ; Sanders et al, 2010 ; Zhang et al, 2011 ; Liu et al, 2012 ; Collins et al, 2018 ; Goncalves et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, these features are not ascribed to elevated cell viability, since the lack of Luzp1 leads to a reduction in cell numbers and additionally, an increase in cell apoptosis. Our results coincide with the reported anti-proliferative effect of Luzp1 downregulation in colorectal cancer cells ( Poel et al, 2019 ) and the reported increase in proliferation due to Luzp1 upregulation in uterine fibroids ( Edwards et al, 2019 ). Considering the interaction between LUZP1 and LIMA1/EPLIN, our results mirror those showing increased metastatic potential upon loss or downregulation of the tumor suppressor EPLIN ( Jiang et al, 2008 ; Sanders et al, 2010 ; Zhang et al, 2011 ; Liu et al, 2012 ; Collins et al, 2018 ; Goncalves et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the exact contribution of LUZP1 in the pathogenesis of the 1p36 syndrome is unknown, it has been proposed to contribute to the development of the cardiovascular malformations ( Zaveri et al, 2014 ; Jordan et al, 2015 ). In addition, a recent study reported that increased LUZP1 expression in the uterus was associated with higher fibroid risk in humans ( Edwards et al, 2019 ). Furthermore, Poel and colleagues claimed that LUZP1 downregulation might mediate chemotherapy sensitivity mechanisms in colorectal cancer cells, potentially through cell cycle arrest ( Poel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although six uterine leiomyoma GWAS have been reported [14][15][16][17][18][19] , recent studies were conducted in European or African American populations. Our group previously reported a GWAS of uterine leiomyoma 18 , but more than 17,000 cases and 75,000 controls were analysed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been six published genome-wide association studies (GWAS) of uterine leiomyoma, and some common single nucleotide polymorphisms (SNPs) associated with leiomyoma risks at 1p36.12 (CDC42/ WNT4) [14][15][16][17] , 1q24.3 (DNM3) 16 , 2p25.1 (GREB1) 14,15,17 , 2p23.2 (BABAM2) 17 , 3p24.1 (NEK10) 14 , 3q26.2 (TERC/ LRRC34) 15,17 , 3q29 15 , 4q12 (SCFD2/LNX1/PDGFRA) 14,15,17 , 4q13.3 (SULT1B1/SULT1E1) 14,15,17 , 4q22.3(PD-LIM5) 17 , 5p15.33 (TERT) 14,15,17 , 5q35.2 (ZNF346) 15,17 , 6p21.31(GRM4/HMGA1) 17 , 6q25.2 (SYNE1/ESR1) [14][15][16][17] , 9p24.33 (KANK1/DMRT1/ANKRD15/LOC105375949) [14][15][16][17] , 10p11.22(ZEB1/ARHGAP12) 17 , 10q24.33 (OBFC1) [14][15][16][17][18] , 11p15.5 (SCGB1C1/BET1L/SIRT3/RIC8A) [14][15][16][17][18] , 11p14.1(FSHB) 17 , 11p13 (WT1/PDHX/...…”
mentioning
confidence: 99%
“…However, hormones are not the only factors influencing those pathophysiological pathways [9,10]. UF development is also largely dependent on genetic factors [11,12], with the disruption of DNA repair mechanisms also playing a role [13]. UFs are markedly more common in dark-skinned women, e.g., African Americans, compared to white women [5,14].…”
Section: Introductionmentioning
confidence: 99%